Creating engaging chemistry lessons: PBL and cooperative learning strategies to combat student boredom in secondary education - Nurfijriati Nurfijriati; Fitriyuni Miralda Siregar; Salamah Agung (EDUSAINS, 2025)
Learning difficulties often hinder students from reaching their academic potential, one of which is caused by boredom during the learning process. This boredom can occur if the teaching methods applied are not sufficiently engaging or relevant to the students. This study aims to explore the implementation of Project-Based Learning (PjBL) and Cooperative Learning models used by chemistry teachers to overcome learning difficulties among 10th-grade students at Madrasah Pembangunan. The research approach used in this study is qualitative with a case study design, in which data were collected through in-depth interviews, classroom observations, and documentation. The results indicate Project-Based Learning (PjBL) and Cooperative Learning models can overcome student difficulties in learning chemistry concepts when combining with differentiated instruction and linking learning to real-life issues. The application of these learning models has been proven to increase student engagement in the learning process and facilitate a deeper and more practical understanding of chemical concepts within the context of their daily lives. This study contributes to enriching chemistry teaching practices at the secondary school level with more innovative and applicable approaches.